NILAI – NILAI SOSIAL DI DALAM PERKAWINAN ADAT DAYAK MAANYAN DI KOTA BANJARMASIN - Marce Diana (Universitas Lambung Mangkurat, 2019)
AbstractThis study aims to: (1) Describe the stages in the Dayak Maanyan traditional marriage in the city of Banjarmsasin (2) Describe the requirements in the Dayak Maanyan traditional marriage in the city of Banjarmasin, (3) Analyze the social values contained in each stage of Dayak Maanyan marriage in the city of Banjarmasin. The method used in this study is descriptive qualitative method with the number of respondents as many as 7 people, 3 key respondents and 4 people supporting respondents. Data collection using interview, observation, documentation and literature study techniques. Data analysis with data reduction, display and verification. The results of this study are: (1) The stages of the Dayak Maanyan customary marriage held in Banjarmasin city consist of the Ngantane/Itunti (introduction) stage, the Adu Pamupuh (engagement) stage, and the Piadu stage (fulfillment of customary law). The most interesting and sacred stage is the Piadu stage because at this time the two brides were officially inaugurated as husband and wife. (2) Requirements in Dayak Maanyan customary marriage in Banjarmasin city. Both the bridegroom and the bride must prepare the requirements of each stage in question. The most prepared requirements are at the Piadu stage, in which there are seven conditions that must be met, namely Tajau Tuak, Keagungan Mantir, Lanjung Ume Pintan Gantung, Eteh Kadiwai, Palangkahan, Tutup Uwan, and Sangku Dite Sangku Lungkung. (3) The Social Values contained in the Dayak Maanyan traditional marriage have at least 8 social values, namely the value of love and appreciation for tradition, the value of sincerity (seriousness) & courage, politeness, family values, values of loyalty, togetherness and mutual cooperation , the value of independence & responsibility, and the values that characterize the Dayak Maanyan, namely the value of kinship. The social values contained in the marriage of the Dayak Maanyan motivated the Dayak Maanyan ethnic population in the city of Banjarmasin to carry out faithfully and genuinely the traditions, especially the indigenous Dayak Maanyan marriage. Keywords: Social Value, Indigenous Marriage, and Dayak Maanyan AbstrakPenelitian ini memiliki tujuan untuk: (1) Mendeskripsikan tahapan dalam perkawinan adat Dayak Maanyan di kota Banjarmsasin (2) Mendeskripsikan persyaratan dalam perkawinan adat Dayak Maanyan di kota Banjarmasin, (3) Menganalisis nilai-nilai sosial yang terkandung dalam tiap tahapan perkawinan adat Dayak Maanyan di kota Banjarmasin. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan jumlah responden sebanyak 7 orang, responden kunci 3 orang dan responden pendukung 4 orang. Pengumpulan data dengan teknik wawancara, observasi, dokumentasi dan studi kepustakaan. Analisis data dengan reduksi data, display dan verifikasi. Hasil dari penelitian ini adalah: (1) Tahapan perkawinan adat Dayak Maanyan yang dilaksanakan di kota Banjarmasin terdiri atas tahap Ngantane/Itunti (perkenalan), tahap Adu Pamupuh (pertunangan), dan tahap Piadu (pemenuhan hukum adat). Tahapan yang paling menarik perhatian dan sakral adalah tahap Piadu karena saat ini lah kedua mempelai diresmikan secara hukum adat sebagai suami istri. (2) Persyaratan dalam perkawinan adat Dayak Maanyan di kota Banjarmasin. Baik pihak mempelai laki-laki maupun perempuan harus menyiapkan persyaratan dari tiap tahapan dimaksud. Persyaratan yang paling banyak disiapkan adalah pada tahap Piadu, didalamnya terdapat tujuh syarat yang harus dipenuhi yaitu Tajau Tuak, Keagungan Mantir, Lanjung Ume Pintan Gantung, Eteh Kadiwai, Palangkahan, Tutup Uwan, dan Sangku Dite Sangku Lungkung. (3) Nilai-Nilai Sosial yang terkandung dalam perkawinan adat Dayak Maanyan sedikitnya ada 8 nilai sosial, yaitu nilai kecintaan dan penghargaan pada tradisi, nilai kesungguhan (keseriusan) & keberanian, nilai kesopanan, nilai kekeluargaan, nilai kesetiaan, nilai kebersamaan & gotong royong, nilai kemandirian & tanggung jawab, serta nilai yang menjadi ciri khas Dayak Maanyan yaitu nilai kekerabatan. Nilai-nilai sosial yang terdapat dalam perkawinan Dayak Maanyan ini memotivasi warga etnis Dayak Maanyan yang ada di kota Banjarmasin untuk melaksanakan dengan setia dan sungguh-sungguh tradisi, khususnya perkawinan adat Dayak Maanyan.Kata kunci: Nilai Sosial , Perkawinan Adat, dan Dayak Maanyan